2019
DOI: 10.1101/617969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A phenome-wide association and Mendelian Randomisation study of polygenic risk for depression in UK Biobank

Abstract: AbstractDepression is the leading cause of worldwide disability but there remains considerable uncertainty regarding its neural and behavioural associations. Depression is known to be heritable with a polygenic architecture, and results from genome-wide associations studies are providing summary statistics with increasing polygenic signal that can be used to estimate genetic risk scores for prediction in independent samples. This provides a timely opportunity to identify traits… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 64 publications
2
21
1
Order By: Relevance
“…In addition to these, PRS were associated with disease and mental health variables, such as MDD, number of depressive episodes and Mood Disorder Questionnaire score. The results indicate that PRS were associated with variables relating to MDD manifestation, as shown in previous studies [ 16 ]. Moreover, although both risk scores were associated with sociodemographic measures, such as years of education and deprivation ranks, MRS had a stronger association than PRS, indicating a stronger role played by the MRS in environmental factors [ 8 12 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition to these, PRS were associated with disease and mental health variables, such as MDD, number of depressive episodes and Mood Disorder Questionnaire score. The results indicate that PRS were associated with variables relating to MDD manifestation, as shown in previous studies [ 16 ]. Moreover, although both risk scores were associated with sociodemographic measures, such as years of education and deprivation ranks, MRS had a stronger association than PRS, indicating a stronger role played by the MRS in environmental factors [ 8 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…Recent phenome-wide association studies have shown that MDD PRS are associated with a range of psychosocial and mental health phenotypes [ 16 ]. Using the same approach, we tested the association between 61 behavioural phenotypes and compared the pattern of association between MRS and PRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, excluding participants with phecodes/diseases related to the investigating phecode/disease in the analysis prevented the contamination of the control population by cases, leading to an increased statistical power ( Wei et al, 2017 ). Our genetic variant-based PheWAS is also advantageous because the genotype is fixed at birth and the results are less susceptible to reverse causality ( Shen et al, 2020 ). The present study also has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were conducted using R (version 3.2.3) in a Linux environment. Linear mixedeffects models (function 'lme' in R package 'nlme') and general linear models (function 'glm' in R package 'stats') were used to investigate structural brain metrics 46,47 . False Discovery Rate (FDR) multiple comparison correction was applied to all bilateral/unilateral structures, lobes and white matter tracts, referred to as PFDR in this report, using the 'p.adjust' function in R and all betas were standardised.…”
Section: Statistical Modelsmentioning
confidence: 99%